RECURRENT ACUTE OTITIS MEDIA lN CHILDREN - Alves, Sandra (2006)
Recurrent Acute Otitis Media is frequent on Otolaryngology daily practice, representing an important amount of office visits during childhood.Given the constant advances on knowledge, from pathophysiology to prevention, the authors perform a global revision, with particular focus on the medical point of view.